Partial purification and properties of cellulase-free alkaline xylanase produced by Rhizopus stolonifer in solid-state fermentation - Goulart, A. J. [UNESP] (2005)
Rhizopus stolonifer was cultivated in wheat bran to produce a cellulase-free alkaline xylanase. The purified enzyme obtained after molecular exclusion chromatography in Sephacryl S-200 HR showed optimum temperature as 45 degrees C and hydrolysis pHs optima as pH 6.0 and 9.0. Xylanase presented higher Vmax at pH 9.0 (0.87 mu mol/mg protein) than at pH 6.0 and minor Km at pH 6.0 (7.42 mg/mL)than at pH 9.0.